An Analysis of Upstream Processes in the Durian Supply Chain: Production Sources, Modes of Transportation and Transport Cost to Local Marketing - photipun, malai; Prakongpak, Poonsiri (Journal for Strategy and Enterprise Competitiveness, 2024)
This study focuses on investigating the upstream processes in the durian supply chain in Chanthaburi Province, focusing on plantation size, production volume, sales models, and transportation to local central markets. The sample group consisted of 393 durian farmers, randomly selected as durian farmers in Chanthaburi Province, who were the group that sold their products in the central market. The research found that most farmers had a planting area between 31-50 rai, accounting for 22.90 percent, with an average production volume of 75.84 tons annually. The most popular sales model was selling to exporters, accounting for 43.82 percent, followed by selling in the local central market, accounting for 34.35 percent. In terms of transportation, it was found that single-cab pickup trucks were the most commonly used vehicles for transporting durian, with an average load capacity of 2,230 kilograms per trip. The average transportation cost for durian was 0.60 baht per kilogram. The data from this research can be used to plan production, marketing, and manage the transportation of durians for maximum efficiency and improve the local fruit supply chain system.